(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. La recente crisi istituzionale dell’Ordine di Malta. Una premessa - 2. La sospensione del Gran Cancelliere: tre versioni a confronto - 3. Dall’intervento della Sede Apostolica alle dimissioni del Gran Maestro - 4. La nomina del Delegato Speciale e l’elezione del Luogotenente di Gran Maestro - 5. Possibili esiti della riforma: il rapporto con la Santa Sede e l’assetto istituzionale dell’Ordine - 6. I Cavalieri melitensi tra professione religiosa e requisiti nobiliari - 7. Verso un esercizio più collegiale della funzione di governo? - 8. Una riforma complessa in un equilibrio delicato. From the 2016-2017 crisis to the constitutional reform of the Sovereign Military Order of Malta ABSTRACT: The paper attempts to examine the recent events surrounding the Sovereign Military Order of Malta and their consequences. On one hand it gives an account of the institutional crisis unfolded since December 2016, which started with the suspension of the Grand Chancellor decreed by the Grand Master. However, following a direct intervention on the matter from the Holy See, the Grand Master resigned from his office and a new Lieutenant was elected in his place. On the other hand it points out the most predictable outcomes of the constitutional reform process launched after the resolution of this crisis, with a particular consideration for the role of the professed Knights in the government of the Order - an aspect which is strictly linked to the relation with the Holy See - and for the balance of powers between the Grand Magistry and the other executive bodies, especially the Sovereign Council.